Revitalisasi Pengembangan Bahasa Indonesia melalui Pemberdayaan Kosakata dan Istilah dalam Era Pasar Bebas - Sri Kusuma Winahyu; Fairul Zabadi (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
As a language used in the realms of science, technology, and art; vocabulary and terms in Indonesian continue to develop along with developments and the needs of the speaking community. So far, vocabulary and terms in Indonesian have not been utilized optimally, giving rise to the impression that the development of Indonesian has stalled. In fact, empowering vocabulary and terms are needed in the free market era. This research aims to describe the development of the Indonesian language through empowering vocabulary and terms, both from regional and foreign languages. The research method uses descriptive qualitative through library research, namely by utilizing books, papers, and other documents related to the focus of writing as data sources. The research data is in the form of vocabulary and terms derived from local languages and foreign languages. The results of the study show that the revitalization of Indonesian language development can be carried out through empowering vocabulary and terms consisting of (1) expansion of vocabulary, (2) utilization of regional languages; (3) utilization of foreign languages, and (4) development of guidelines and policies. It is hoped that the results of this research will be able to help develop the Indonesian language through empowering vocabulary and terms in regional and foreign languages.